The Master of Instructional Design & Technology, Open University Malaysia - Jasemaine Gan; Open University Malaysia; veryimaginativepeeps
Professor Dr Abtar Kaur, the lead facilitator & programme coordinator for the Master of Instructional Design & Technology (MIDT) has kindly invited me to produce a video for her.